Cyclicality of commodity markets with respect to the U.S. economic policy uncertainty based on granger causality in quantiles. (21st October 2020) - Apergis, Nicholas; Hayat, Tasawar; Saeed, Tareq
Abstract: Given the importance of the U.S. in global commodity markets, the goal is to explore whether U.S. economic policy uncertainty impacts the price performance of certain commodities. The analysis uses the Granger causality in quantiles method that allows us to test whether there are different effects under different market conditions. The results document that economic uncertainty impacts the returns on the commodities considered, with the effects clustering around the tail of their conditional distribution. Robust evidence was obtained under alternative definitions of uncertainty.